'Sancta Caecilia Rediviva'. Elizabeth Linley: repertoire, reputation and the English voice - Aspden, S (Cambridge University Press, 2015)
Whether we think of an aria as a ‘miniature’ or not, the analyst’s temptation to synecdoche is ever-present: great arias can, at times, stand for great operas or their composers, just as great composers have stood for their epochs. While monumentalising the composer is now passé, the lapidary quality of a much-loved aria still invites singular attentiveness. When the arias and operas are not canonic familiars, however, their distillatory comfort is denied us – we must instead view the piece from less customary perspectives.